Sisterhood in Academia - Storying our Experiences in Higher Education - Nereshee Govender; Nonhlanhla Khumalo; Grace Temiloluwa Agbede (African Journal of Inter-Multidisciplinary Studies)
Breaking the barriers for women in higher education institutions has been on the global agenda for over a decade. Women's lived experiences in academia has notably focused on issues of inequality and systemic gendered barriers that lead to women opting out of academia. This study acknowledges that many black women academics feel caged and overlooked in their positions and argues that despite these challenges, women are resilient and need to carve out spaces to navigate their paths in the academy. Using the autoethnography inquiry approach, we reflect on how our experiences shaped our academic journey in higher education institutions. The principles of Communities of Practice (CoP) is adopted as a framework underpinning this paper. It is envisaged that this framework will help examine the challenges and opportunities black women academics experience in higher education. Our reflective discussion on the sisterhood we embraced during our academic journeys has suggested that institutions need to provide mentorship opportunities, and spaces to talk, support and be supported.